Verification and Examination Management of Complex Systems - Ruud, Stian Knud; Skjetne, Roger (Modeling, Identification and Control: A Norwegian Research Bulletin, 2014)
As ship systems become more complex, with an increasing number of safety-critical functions, many interconnected subsystems, tight integration to other systems, and a large amount of potential failure modes, several industry parties have identified the need for improved methods for managing the verification and examination efforts of such complex systems. Such needs are even more prominent now that the marine and offshore industries are targeting more activities and operations in the Arctic environment. In this paper, a set of requirements and a method for verification and examination management are proposed for allocating examination efforts to selected subsystems. The method is based on a definition of a verification risk function for a given system topology and given requirements. The marginal verification risks for the subsystems may then be evaluated, so that examination efforts for the subsystem can be allocated. Two cases of requirements and systems are used to demonstrate the proposed method. The method establishes a systematic relationship between the verification loss, the logic system topology, verification method performance, examination stop criterion, the required examination effort, and a proposed sequence of examinations to reach the examination stop criterion. (c)2014 Norwegian Society of Automatic Control. Published with the Creative Commons Attribution 3.0 Unported (CC BY 3.0) license. See: http://creativecommons.org/licenses/by/3.0/.